Editorial - Maya Sánchez, Mario (Boletín Geológico, 2021)
Boletín Geológico has published issue 48(1), June 2021, with articles on economic geology, structural geology, and basin evolution (Figure 1). Arrubla & Silva characterize and classify the gold ore mineral occurrences related to the main intrusive centers of the El Cerro Igneous Complex: Cerro Frontino, Morrogacho and La Horqueta. Information about the distribution, ore mineralogy, structural geology, lithological patterns and gold mineral chemistry of the associated deposits is provided. The authors present the metallogenic characterization of the complex based on petrological and fieldwork data carried out in intrusive bodies and descriptions of the mineralogical, structural and hydrothermal features of gold mineralizations. Amaya et al. present a lithological, petrographic, geochemical, and geochronological characterization of the San José de Guaviare Syenite (SJGS), unit exposed in an area with Precambrian plutonic igneous and metamorphic rocks, which belong to the crystalline basement of the NW Amazonian Craton. The SJGS consists of nepheline syenites, nepheline monzosyenites, nepheline-bearing alkali-feldspar syenites, syenites, quartz-syenites, quartz-alkali-feldspar syenites, syenogranites, and quartz-rich granitoids. The SJGS intrusion generated a thermal metamorphism, in amphibolite and pyroxene-hornfels facies, in the host rocks of the Guaviare Complex. Forero et al. propose a methodology for the identification, mapping and analysis of the nature of faults and shear zones. They suggest to characterize structures and fault rocks, define the structural level observed, determine the movement’s distribution and kinematics, and assign the relative and absolute ages of deformation, in order to propose some minimum parameters necessary to perform geological-structural studies for acquiring basic information that aids understanding of the tectonic evolution. López et al. propose a scheme for recording data acquired in the field in a table, which enables sorting by type of fabric element (planar or linear), and the recording of the lineaments always in front of the plane that contains them. In addition, the recording scheme includes data corresponding to the kinematics or direction of movement of faults and shear zones, the indicators that support the kinematics, and a qualitative assessment of the certainty or reliability of the kinematics assigned to the direction of shear zone movement. Rosello et al. propose a working hypothesis that will generate interest in promoting exploration activities and basic research to confirm or reject a new hydrogeological potential located at greater depths and beneath the structure commonly known as the Puelches aquifer, Argentina. Boletín Geológico acknowledges the collaboration of the following reviewers and their commitment to the peer-review process involved in this issue: Umberto Cordani - Universidade de São Paulo, Brazil. Salomon Kroonenberg - Delft University of Technology, The Netherlands. Maria Helena Bezerra de Hollanda - Universidade de São Paulo, Brazil. Uwe Martens - Universidad Nacional Autónoma de México, México. Eduardo Kruse - Universidad Nacional de La Plata, Argentina. José Duque Trujillo - Universidad EAFIT, Colombia. Hernán Barcelona - Universidad de Buenos Aires, Argentina. Ethel Morales - Universidad de la República, Uruguay. Marcos Roberto Pinheiro - Universidade de São Paulo, Brazil. Bruno Vieira Ribeiro - Monash University, Australia. Carlos Mario Echeverri - Universidade Federal de Campina Grande, Brazil. Paola Botero Santa - Universidad Nacional Autónoma de México, México. Orlando Hernández - Universidad Nacional de Colombia, Colombia. Leonardo Mairink Barão - Universidade Federal do Paraná, Brazil. Guillermo Camargo - Universidad Nacional de Colombia, Colombia. Diego Gómez - Universidad EAFIT, Colombia.